PENGARUH HARGA MENGASUH ANAK TERHADAP PARTISIPASI KERJA WANITA MENIKAH DI INDONESIA - Sukma Direja; Diah Widyawati (FEB Universitas Sultan Ageng Tirtayasa, 2018)
ABSTRACTThe existence of young children is estimated to increase the reservation wages of a mother, this can reduce the possibility of their work participation in entering the labor market. This study aims to determine the effect of childcare price on the work participation of women who are married in Indonesia. Estimation of labor participation in this study uses a bivariate probit model in whichdecisions on work decisions are taken simultaneously with decisions on the choice of care type for women who are married. Because not all mothers in the sample work and use paid childcare, childcare wages and prices are estimated for all mothers. To overcome the sample selection bias,the two-stage Heckman method was used. The results of this study indicate that the price of childcare negatively affects the work participation of married women. Which means that if there is an increase in the price of caring a child, it will reduce the work participation of married women.Kata Kunci: Partisipasi kerja wanita, harga mengasuh anak